Characterization and analysis of Fe-Co based hybrid composites. (2021) - Raghav, G.R.; Suraj, R.; Chandran, Vidya; Sujith, R.; Dev, Amal P.; Vishnu, H.
Abstract: In this study, powder metallurgy process has been made use for making the Fe-Co based hybrid composites. Different compositions of Chromium in the hybrid composites were tested for its tribological properties. Also the mechanical properties of the hybrid composites were studied to get an understanding about the durability of the composites at different compositions. The tests used were Wear analysis, Corrosion analysis and hardness analysis. Pin on Disc apparatus was used for the analysis of wear of the hybrid composites. Corrosion analysis was done using the weight loss method. The morphological analysis was carried out using Scanning Electron Microscope (SEM) to get an understanding about the material constituents. The compressive strength of Fe-20Co-10Cr hybrid composites exhibited a compressive strength of 253 HV which is 20% higher compared to Fe-20Co composites. The density of the Fe-20Co-10Cr hybrid composites has improved with the addition of Cr. The Microhardness of the Fe-20Co hybrid composites has increased to 145 HV with 10% addition of Cr reinforcement. There was a variation in the corrosion rate and wear rate with the varying compositions. The properties tend to get better with a higher concentration of Chromium in the composites. Higher Chromium content improved the Wear resistance as well as the corrosion resistance.